Does action make you faster? A retrieval-based approach to investigating the origins of the enactment effect - SPRANGER, TINA; SCHATZ, TANJA R.; KNOPF, MONIKA (Scandinavian journal of psychology, 2008)
The enactment effect, the stable finding that memory for action phrases is enhanced in a subject‐performed compared to a verbal task (SPT; VT), has repeatedly been demonstrated. The question remains whether the enactment effect has to do with specific characteristics of the SPT‐retrieval process. Experiment 1 tested younger and older adults in a within‐subjects design with two direct free recall tests. Thorough analyses of the recall process showed that the benefit from self‐performing the items becomes apparent early into the retrieval phase for both age groups. Experiment 2 tested the same age groups with a retention phase of 30 minutes. The same general results pattern emerged. The acceleration of the recall process in SPTs is indicative of a heightened accessibility of the actively encoded material, making it less susceptible to forgetting. This property of SPTs must be taken into account when trying to determine the origins of the enactment effect.